Faktor yang Mempengaruhi Penyalahgunaan NAPZA di Masyarakat - Rahmi Indiani; Siti Nurazizah AH; Mochamad Bhagas Abdulah; Rivandia Listi (Sistem Informasi, 2022)
Deaths due to drugs in Indonesia are estimated at 50 people per day. This causes the problem of drug abuse to become a priority. BNN continues to act to prevent the spread of drugs in the community to prevent further spread, such as looking for drug trafficking networks. However, drug abuse and drug distribution by irresponsible persons persists and this problem persists in the community. This study aims to find out what factors can cause people to abuse drugs by using the literature study method. The results found that the factors of drug abuse are personality, family, economy, environment, age and gender. Therefore, the role of the community is needed to prevent drug trafficking and drug abuse in the immediate environment by looking at the factors that can lead to drug abuse so that drug deaths can be reduced.